2015
DOI: 10.1017/s1368980015000075
|View full text |Cite
|
Sign up to set email alerts
|

Setting goal and implementation intentions in consultations between practice nurses and patients with overweight or obesity in general practice

Abstract: Objective: Patients with overweight or obesity increasingly attend general practice, which is an ideal setting for weight-loss counselling. The present study is the first to investigate the quality of weight-loss counselling provided by practice nurses in general practice to patients with overweight or obesity, in order to identify points for improvement. Design: An observational checklist was developed to assess goal and implementation intentions and 'missed opportunities for lifestyle counselling'. Compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…It provides a sequence of evidence-based practice behaviors that are effective in helping patients to change health behaviors (33)(34)(35)(36). It can also be used for quality improvement (34 We also investigated the use of goal and implementation intentions to assess the quality of weightloss counselling provided by PNs to overweight or obese patients (160). Half of the consultations contained a goal intention; the majority aimed to change eating behaviour.…”
Section: Practice Nurses (Pns) In Primary Carementioning
confidence: 99%
“…It provides a sequence of evidence-based practice behaviors that are effective in helping patients to change health behaviors (33)(34)(35)(36). It can also be used for quality improvement (34 We also investigated the use of goal and implementation intentions to assess the quality of weightloss counselling provided by PNs to overweight or obese patients (160). Half of the consultations contained a goal intention; the majority aimed to change eating behaviour.…”
Section: Practice Nurses (Pns) In Primary Carementioning
confidence: 99%
“…They are trained to provide more detailed guidance on lifestyle changes, by means of communication techniques such as motivational interviewing. However, it has been shown that they could improve the quality of their lifestyle counselling so as to have more impact, which should also be more fully integrated in their training programme [30].…”
Section: Obesity Carementioning
confidence: 99%
“…Video observation in primary care research focuses on the interaction between the practitioner and the patient, and technology or other personnel in the primary care team (Pearce et al, 2006, Spelten et al, 2015. In doing so, rich verbal, nonverbal and para-verbal communication may be extracted for analysis which assists researchers to understand the dynamics and communication techniques, skill development, and engagement in reflective practice in order to improve patient and professional interactions and outcomes (Asan and Montague, 2014, Macdonald et al, 2013, van Dillen et al, 2014a, Van Dillen et al, 2014b, Van Dillen et al, 2015, Verbiest et al, 2014.…”
Section: Advantages Of Video Observationmentioning
confidence: 99%